Analysis of pension systems : Public and private funding comparison - Kostrhoun, Tomáš; Zamrazilová, Eva, 1961-; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
In the first part of the thesis, individual pension systems are reviewed and analysed. Research of available literature is used as a major method in this part. We examine the advantages and disadvantages of each from the perspective of both public expenditures and pensioners.The second part of the thesis pension replacement rate employing fixed time effects regression. Thesis analyses OECD countries in the time period 2000 to 2018. We use data available in OECD, IMF, and World Bank libraries. In the latter part of the thesis, we examine private saving possibilities as a complement to pension benefits provided by the government. Future value of the annuity is used to estimate monthly contributions to savings account necessary to maintain the standard of living.We conclude that due to the adverse demographic projections, the governments are not able to maintain the pension replacement rate and not to increase budget deficit simultaneously.In the last part of the thesis, we present specific private pension saving possibilities that will provide the future pensioners’ with another income stream and thus will increase their standard of living.
Vedoucí práce: Eva Zamrazilová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses